Lean management systems: creating a culture of continuous quality improvement. Issue 8 (11th June 2013) - Clark, David M; Silvester, Kate; Knowles, Simon
Abstract : This is the first in a series of articles describing the application of Lean management systems to Laboratory Medicine. Lean is the term used to describe a principle-based continuous quality improvement (CQI) management system based on the Toyota production system (TPS) that has been evolving for over 70 years. Its origins go back much further and are heavily influenced by the work of W Edwards Deming and the scientific method that forms the basis of most quality management systems. Lean has two fundamental elements - a systematic approach to process improvement by removing waste in order to maximise value for the end-user of the service and a commitment to respect, challenge and develop the people who work within the service to create a culture of continuous improvement. Lean principles have been applied to a growing number of Healthcare systems throughout the world to improve the quality and cost-effectiveness of services for patients and a number of laboratories from all the pathology disciplines have used Lean to shorten turnaround times, improve quality (reduce errors) and improve productivity. Increasingly, models used to plan and implement large scale change in healthcare systems, including the National Health Service (NHS) change model, have evidence-based improvement methodologies (such as Lean CQI) as a core component. Consequently, a working knowledge of improvement methodology will be a core skill for Pathologists involved in leadership and management.